Validating the Technology Proficiency Self-Assessment Questionnaire for 21st Century Learning (TPSA C-21). Issue 1 (2nd January 2017) - Christensen, Rhonda; Knezek, Gerald
Abstract: Accurately measuring levels of technology proficiency in current and future classroom teachers are an important first step toward enhancing comfort level and confidence in integrating technology into the educational environment. The original Technology Proficiency Self-Assessment (TPSA) survey has maintained respectable psychometric properties for more than 15 years in assessing educator self-efficacy regarding skills for integrating technology into classroom teaching and learning. An updated version of the TPSA with new items related to emerging technologies, including mobile technologies, is shown to remain a reliable and valid instrument worthy of use with preservice and in-service educators for planning professional development related to technology integration.